Profil Kemampuan Literasi Numerasi Siswa dengan Gaya Kognitif Verbalizer-Imager dan Alternatif Strategi Pembelajarannya - Dahlia, Dini; Pujiastuti, Heni; Mutaqin, Anwar (Academy of Education Journal, 2025)
Numeracy literacy is an essential 21st‑century skill, yet Indonesian students continue to face difficulties in reasoning and applying mathematical concepts in real‑world contexts. This study aims to describe the numeracy literacy profiles of senior high school students based on verbalizer-imager cognitive styles and to formulate alternative learning strategies suited to these characteristics. A descriptive qualitative approach was employed with 12 grade‑X students from two public senior high schools in Serang Regency, purposively selected based on their numeracy literacy levels (high, medium, low) and cognitive styles. Data were collected through numeracy literacy tests, cognitive style questionnaires, and semi‑structured interviews, then analyzed using Miles and Huberman’s model with the assistance of NVivo 12 Plus. The findings indicate that verbalizer students rely on narratives but struggle with visual interpretation, while imager students excel in visualization yet require reinforcement of numerical concepts. These differences influence their problem‑solving strategies, highlighting the need for adaptive multimodal learning that integrates narratives, visualization, and reflection to enhance numeracy literacy.